Identificação de critérios de seleção de conteúdos para o arquivamento da Web - Formenton, Danilo (Universidade Federal de São Carlos, 2023)
With the significant increase in production, diffusion and consumption of digital content in the Web environment, actions for the recovery, preservation and communication of data and information, of scientific, cultural and historical value produced in websites, social media and other Web-based content, are being created and studied in face of the ephemerality of the Internet that imposes rapid changes or even permanent losses to informational resources. Digital preservation and archiving of Web-based content is a recent theme in Brazil, specifically discussed in Information Science and, in general, not contemplated in the field of Science, Technology and Society (STS), being necessary the interdisciplinary transit with Information Science. In this context, we aim to verify how criteria for selecting Web content in the context of digital preservation and Web archiving have been discussed by Information Science and related areas (Archivology, Librarianship and Museology), pointing out how these criteria could meet the demands for structuring institutional Web archives in a more adequate way for the long-term preservation of digital information. As methodology, an exploratory study was carried out, based on bibliographic and documentary research with a narrative literature review concerning Web archiving in the scope of digital preservation. Content analysis was applied to Web content selection criteria and policies identified in the literature for digital preservation and long-term archiving purposes. As a result, a theoretical, technical and systematized framework of selection criteria applicable to Web archiving and digital preservation is presented, based on the surveyed scientific literature and on policies from various Web archiving initiatives around the world, such as criteria for "old" and "current" sites, geographic and linguistic criteria, subject-related criteria, criteria based on Web archiving uses and its users or experts, or format-related criteria, and, simultaneously, that may be relevant for modeling institutional Web archive collections. It was found that the imperfection of the Web archiving process and the incompleteness of its products, that is, the Web archives, in terms of the completeness of the archived sites, stems not only from technical, temporal, budgetary or legal limits, but also from limits tied to selection decisions. The selection decisions adopted in Web archiving policies bring some degree of subjectivity and deliberation, which can be avoided by explicitly justifying the criteria in a selection policy, making the archiving and its final product (collections) coherent. Furthermore, within the development of a Web archiving selection policy, it was possible to verify that in the scopes of the selection methods adopted in the creation of Web collections, in the scope, coverage of the archiving and the target (extent) of the collection itself, in the definition of the type and means of access of the Web archive, and in the definition of the expected uses of the Web archive and the intended users, different criteria for the selection of contents agreed upon in the policy are delineated.
Identification of content selection criteria for Web archiving
Identificación de criterios de selección de contenido para archivo Web
Keywords: Arquivamento da Web; Preservação digital; Gestão de conteúdos na Web; Critérios de seleção; Desenvolvimento de coleções; Web archiving; Digital preservation; Web content management; Selection criteria; Collection management; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO; CIENCIAS SOCIAIS APLICADAS